A polyimide-based shape memory composite aerogel and preparation method thereof

By using the composite technology of polyimide and graphene oxide in shape memory aerogels, the problem of insufficient performance of existing shape memory aerogels in high temperature environments is solved, and higher transition temperature, better mechanical properties and stronger shape memory capabilities are achieved.

CN116218018BActive Publication Date: 2025-02-28JIANGNAN UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210053126.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-18
Publication Date
2025-02-28
Estimated Expiration
2042-01-18

AI Technical Summary

Technical Problem

Existing shape memory aerogels have problems with poor mechanical properties, low transition temperature and poor shape memory performance, especially in high temperature environments.

Method used

Condensation polymerization is performed using diamine and dianhydride monomer to obtain a polyimide precursor polyamic acid gel, and the carboxyl group is protected by triethylamine, followed by solvent exchange and drying, and finally blended with graphene oxide. After freeze-forming and high-temperature treatment, a polyimide/reduced graphene oxide composite aerogel is prepared.

Benefits of technology

The transition temperature of the shape memory aerogel is improved, making it suitable for high-temperature environments, enhancing its mechanical properties and corrosion resistance, while reducing the volume shrinkage rate and improving the shape memory performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116218018B_ABST
    Figure CN116218018B_ABST
Patent Text Reader

Abstract

The present invention discloses a polyimide-based shape memory composite aerogel and a preparation method thereof, and belongs to the field of polymer-based nanocomposite materials. The present invention prepares a polyimide / reduced graphene oxide composite aerogel with shape memory properties for the first time, uses diamine and dianhydride monomers for condensation polymerization to obtain a polyamic acid gel, solvent exchange in water to obtain polyamic acid, and then blends it with graphene oxide in water to form a blended suspension, injects it into a mold for freeze molding, and freeze-dries to obtain a polyamic acid / graphene oxide composite aerogel; then high-temperature treatment is performed to obtain a polyimide-based shape memory composite aerogel. The shape memory aerogel prepared by the present invention has the advantages of low density, high porosity, high deformation temperature and good shape memory performance, filling the current gap in the field of high temperature resistant shape memory aerogel materials, and at the same time solves the shortcomings of high volume shrinkage and poor thermal conductivity in the current preparation process of polyimide aerogel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer-based nanocomposite materials, and in particular relates to a polyimide-based shape memory composite aerogel and a preparation method thereof. Background Art

[0002] Aerogel is a type of solid material with extremely low density, also known as dry gel. Aerogel has the advantages of high porosity, high specific surface area, and high temperature resistance due to its highly permeable three-dimensional microscopic network structure. It is widely used in aerospace, thermal insulation materials, sound insulation materials, flame retardant materials, flexible materials, shock absorbing materials, and energy storage devices. Since the advent of silica aerogel in 1931, after nearly a century of development, researchers from all over the world have successfully prepared a variety of aerogel materials, including silicon oxide, aluminum oxide, titanium oxide, iron oxide, sulfide and organic polymer aerogel materials. Among them, organic polymer aerogel can be sintered under an inert gas protective atmosphere to prepare carbon aerogel materials. Aerogel materials have always been a hot spot in scientific research due to their structural diversity and excellent performance.

[0003] Shape memory polymers (SMPs) are polymers that can restore their original shape from a temporary shape when exposed to various external stimuli (e.g., electric current, pH, humidity, magnetic field, heat, and light). This "memory" property of SMPs makes them widely used in various fields, such as textiles, packaging, medical, and aerospace. SMPs are structurally composed of two parts; a stationary phase that can maintain a permanent shape and a reversible phase that maintains a temporary shape. For SMPs that respond to thermal stimuli, their shape transition temperature is usually the glass transition temperature (T) of the amorphous phase. g ) and the melting temperature of the crystalline phase (T m ). The first proposal of SMP was disclosed in a patent in 1941 as methacrylate for dental applications.

[0004] Polyimide is a type of high-performance polymer with the characteristics of high thermal stability, excellent mechanical properties and low dielectric constant. Due to its excellent performance, polyimide materials are widely used in aerospace materials, automotive materials, and various electronic devices. In recent years, the shape memory properties of polyimide materials have also been discovered by researchers. Researchers have conducted a lot of research on shape memory polyimide, and prepared multifunctional shape memory polyimide materials through structural design, such as high temperature resistant shape memory polyimide, optically transparent shape memory polyimide, and shape memory polyimide with electromagnetic shielding properties. However, the current reports on shape memory polyimide are mostly focused on polyimide film materials.

[0005] Shape memory aerogel is a new type of shape memory material. It combines shape memory materials with aerogel materials, giving full play to the advantages of aerogel materials and shape memory materials and expanding their scope of application. At present, people have little research on high-performance and high-temperature resistant shape memory aerogels, and the current shape memory aerogels have problems such as poor mechanical properties, low transition temperature and poor shape memory performance. If polyimide can be used in the field of shape memory aerogel materials, it is expected to solve many problems of current shape memory aerogels. At present, related research based on this is still blank. Summary of the invention

[0006] The purpose of the present invention is to improve the shortcomings of shape memory aerogel such as low transition temperature and poor heat resistance, while improving the disadvantages of large volume shrinkage of polyimide aerogel, further improve the shape memory performance of polyimide aerogel, and provide a shape memory composite aerogel and a preparation method thereof.

[0007] The invention provides a shape memory composite aerogel and a preparation method thereof. The method comprises the following steps: condensing and polymerizing diamine and dianhydride monomers to obtain a polyimide precursor polyamic acid gel, protecting a carboxyl group with triethylamine, slowly flowing the obtained polyamic acid gel into ultrapure water and stirring, performing solvent exchange, drying the polyamic acid after solvent exchange, dissolving the dried polyamic acid and graphene oxide in ultrapure water, stirring, injecting the mixed suspension into a mold, placing the mold in a freezer for freeze molding, placing the mold in a freeze dryer for drying after molding to obtain a polyamic acid / graphene oxide composite aerogel, and performing high temperature treatment on the polyamic acid / graphene oxide composite aerogel to obtain a polyimide / reduced graphene oxide composite aerogel with shape memory performance.

[0008] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0009] A method for preparing a polyimide-based shape memory composite aerogel comprises the following steps:

[0010] (1) a diamine monomer and a dianhydride monomer are subjected to a polycondensation reaction in N-methylpyrrolidone (NMP) to obtain a polyamic acid gel which is a polyimide precursor;

[0011] (2) placing the obtained polyamic acid gel in water for solvent exchange, and then freeze-drying the gel to obtain polyamic acid filaments;

[0012] (3) dispersing the obtained polyamic acid filaments and graphene oxide in water, mixing them evenly, to obtain a mixed dispersion;

[0013] (4) injecting the obtained mixed dispersion into a mold, placing the mold in a freezer for freeze molding, and freeze drying after molding to obtain a polyamic acid / graphene oxide composite aerogel;

[0014] (5) The obtained polyamic acid / graphene oxide composite aerogel is subjected to high temperature treatment to obtain a polyimide / reduced graphene oxide composite aerogel, that is, a polyimide-based shape memory composite aerogel.

[0015] In one embodiment of the present invention, in step (1), the diamine monomer is 4,4'-diaminodiphenyl ether (ODA).

[0016] In one embodiment of the present invention, in step (1), the dianhydride monomer is biphenyltetracarboxylic dianhydride (BPDA).

[0017] In one embodiment of the present invention, in step (1), the molar ratio of the diamine monomer to the dianhydride monomer is 1:(0.8-1.5); specifically, it can be 1:1.01-1.20.

[0018] In one embodiment of the present invention, in step (1), the polycondensation reaction is carried out in an ice bath.

[0019] In one embodiment of the present invention, in step (1), the polycondensation reaction time is 12 to 24 hours.

[0020] In one embodiment of the present invention, in step (1), the amount of N-methylpyrrolidone added relative to the diamine is 3-5 mL / mol of diamine.

[0021] In one embodiment of the present invention, in step (1), the polycondensation reaction further comprises adding triethylamine after 3 hours of reaction. The molar ratio of triethylamine to diamine monomer is 1:(0.3-3.5).

[0022] In one embodiment of the present invention, in step (2), the solvent exchange time is 3 to 5 minutes.

[0023] In one embodiment of the present invention, in step (3), the stirring time for mixing is 3 to 6 hours.

[0024] In one embodiment of the present invention, in step (3), the stirring speed for mixing is 500 to 1000 rpm.

[0025] In one embodiment of the present invention, in step (3), the mass ratio of graphene oxide to polyamic acid filaments in the mixed dispersion is 1:(1-9); specifically preferably 1:4.

[0026] In one embodiment of the present invention, in step (3), the mass fraction of graphene oxide in the mixed dispersion is 0.2%-1.0%; specifically, 0.5% may be selected.

[0027] In one embodiment of the present invention, in step (4), the freezing molding temperature is -120 to -50°C.

[0028] In one embodiment of the present invention, in step (4), the freezing molding time is 3 to 8 hours.

[0029] In one embodiment of the present invention, in step (4), the freeze-drying time is 48 to 96 hours.

[0030] In one embodiment of the present invention, in step (4), the temperature of the freeze dryer is -90 to -60°C.

[0031] In one embodiment of the present invention, in step (5), the high temperature treatment is performed at a temperature of 100 to 350° C. and for a time of 1 to 3 hours.

[0032] In one embodiment of the present invention, in step (5), the high temperature treatment may be carried out at the following temperature: 100-150°C for 0.5-1.5h, 200-250°C for 0.5-1.5h, and 300-350°C for 0.5-1.5h.

[0033] In one embodiment of the present invention, in step (5), the high temperature treatment needs to be performed under an inert atmosphere.

[0034] In one embodiment of the present invention, in step (5), the equipment for high temperature treatment is a tubular furnace, and the treatment is carried out under an argon atmosphere.

[0035] The present invention provides a polyimide-based shape memory composite aerogel based on the above preparation method.

[0036] The present invention also provides the use of the polyimide-based shape memory composite aerogel in the preparation of thermal insulation materials, sound insulation materials, flame retardant materials, flexible materials, shock absorbing materials and energy storage devices.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] (1) The present invention prepares shape memory polyimide aerogel for the first time, which has a simple preparation process, low cost, good formability, and the shape of the aerogel can be designed, which is suitable for use in a variety of application environments.

[0039] (2) The polyimide used in the present invention is a type of high-performance polymer. The aerogel prepared by the present invention has the advantages of good mechanical properties, high temperature resistance and corrosion resistance. At the same time, since the glass transition temperature of polyimide is as high as 250°C or above, the shape transition temperature of the aerogel prepared by the present invention is the highest among the currently known shape memory aerogels, which makes the aerogel material prepared by the present invention can be used in a variety of extremely harsh environments, such as the aerospace field.

[0040] (3) The present invention reduces the volume shrinkage rate during the preparation of polyimide aerogel by introducing graphene oxide and polyimide for compounding. Graphene oxide and polyimide are uniformly compounded, and polyimide molecular chains are uniformly distributed in the graphene sheets, thereby enhancing the rigidity of the polymer, enabling it to resist the pressure during the vacuum drying process and the thermal shrinkage stress during the high-temperature imidization process of polyamic acid, while also enhancing the restoring force of the shape memory process.

[0041] (4) The graphene oxide added in the present invention will also be reduced during the high-temperature imidization process of the composite aerogel to obtain reduced graphene oxide with better thermal conductivity, thereby improving the overall thermal conductivity of the composite aerogel, helping the composite aerogel to reach the transition temperature faster, and facilitating the acceleration of the shape memory response time. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is a microstructure diagram of the shape memory polyimide composite aerogel prepared in Comparative Example 1;

[0043] Figure 2 A microstructure diagram of the shape memory polyimide / reduced graphene oxide composite aerogel prepared in Example 1;

[0044] Figure 3 This is a physical display diagram of the shape recovery process during the shape memory performance test of the shape memory polyimide / reduced graphene oxide composite aerogel prepared in Example 1;

[0045] Figure 4 This is a diagram showing the results of quantitatively testing the shape memory performance of the shape memory polyimide / reduced graphene oxide composite aerogel prepared in Example 1 using a dynamic thermal mechanical analyzer. DETAILED DESCRIPTION

[0046] The present invention is further described in detail below in conjunction with specific embodiments, but the embodiments of the present invention are not limited thereto. For process parameters not particularly noted, conventional techniques may be used.

[0047] Example 1

[0048] (1) Weigh 10 mmol ODA and 10.5 mmol BPDA. First, add 10 mmol ODA to 35 ml NMP in an ice bath and stir to dissolve. After dissolution, add 10.5 mmol BPDA in 5 equal portions and react for 3 hours. Then, add 3.1 ml triethylamine and continue to react for 9 hours to obtain a viscous polyimide precursor polyamic acid gel, which is placed in a refrigerator for aging for 24 hours before use.

[0049] (2) taking a large amount of ultrapure water and placing it in an ice bath, slowly pouring the polyamic acid gel obtained in the above step 1 into the ultrapure water and stirring it to obtain a filamentous gel, stirring it thoroughly, freezing the obtained filamentous gel at -20°C for 24 hours to obtain a frozen polyamic acid gel, placing it in a freeze dryer for freeze drying, and taking it out after 72 hours to obtain dry polyamic acid filaments;

[0050] (3) dissolving 0.4 g of the polyamic acid filaments obtained in step 2 in 20 ml of water, and adding 0.2 g of triethylamine to accelerate the dissolution, to obtain a polyamic acid aqueous solution; adding 0.1 g of graphene oxide to the polyamic acid aqueous solution, stirring thoroughly, to obtain a mixed dispersion of polyamic acid and graphene oxide;

[0051] (4) pouring the mixed dispersion of polyamic acid and graphene oxide obtained in the above step 3 into a mold, placing the mold in a freezer, freezing at -70°C for 3 hours, and then placing the mold in a freeze dryer for freeze drying to obtain a polyamic acid and graphene oxide composite aerogel;

[0052] (5) The polyamic acid and graphene oxide composite aerogel obtained in the above step 4 is placed in a tubular furnace, and the polyamic acid is imidized and the graphene oxide is reduced by high temperature in an argon atmosphere. The high temperature treatment temperature program is 100° C. for 1 hour, 200° C. for 1 hour, and 300° C. for 1 hour, and finally a polyimide / reduced graphene oxide composite aerogel is obtained.

[0053] The properties of the obtained polyimide / reduced graphene oxide composite aerogel were measured, and the results are shown in Table 1-2.

[0054] Table 1 Performance results of the obtained polyimide / reduced graphene oxide composite aerogel

[0055] Shape memory aerogel transition temperature (℃) Decomposition temperature(℃) Shrinkage rate (%) 311 620 16.01

[0056] Table 2 Shape memory performance results of the obtained polyimide / reduced graphene oxide composite aerogel

[0057]

[0058] Shrinkage rate determination process: The diameter changes of the aerogel before and after drying were measured respectively, and the calculation formula was: Shrinkage rate (%) = (d0-d) / d0; wherein d and d0 represent the diameters of the wet gel and the aerogel, respectively.

[0059] Fixation rate determination process: Dynamic thermomechanical analysis technology is used to test the shape memory behavior of aerogel under compression mode, and the shape fixation rate of aerogel shape memory process is obtained through test data analysis. The calculation formula is: Fixation rate (%) = (ε unload -ε0) / (εload -ε0); where ε load represents the maximum strain under load, ε0 is the initial strain, and ε unload is the fixed strain after cooling and unloading.

[0060] Recovery rate determination process: Dynamic thermomechanical analysis technology is used to test the shape memory behavior of aerogel under compression mode, and the shape recovery rate of aerogel shape memory process is obtained through test data analysis. The calculation formula is: Recovery rate (%) = (ε unload -ε rec ) / (ε load -ε0); where ε load and ε rec represents the maximum strain and recovery strain under load, ε0 is the initial strain, ε unload is the fixed strain after cooling and unloading.

[0061] Comparative Example 1: No graphene added

[0062] (1) Weigh 10 mmol ODA and 10.5 mmol BPDA. First, add 10 mmol ODA to 35 ml NMP in an ice bath and stir to dissolve. After dissolution, add 10.5 mmol BPDA in 5 equal portions and react for 3 hours. Then, add 3.1 ml triethylamine and continue to react for 9 hours to obtain a viscous polyimide precursor polyamic acid gel, which is placed in a refrigerator for aging for 24 hours before use.

[0063] (2) taking a large amount of ultrapure water and placing it in an ice bath, slowly pouring the polyamic acid gel obtained in the above step 1 into the ultrapure water and stirring it to obtain a filamentous gel, stirring it thoroughly, freezing the obtained filamentous gel at -20°C for 24 hours to obtain a frozen polyamic acid gel, placing it in a freeze dryer for freeze drying, and taking it out after 72 hours to obtain dry polyamic acid filaments;

[0064] (3) dissolving 0.5 g of the polyamic acid filaments obtained in step 2 in 20 ml of water, and adding 0.25 g of triethylamine to accelerate the dissolution, to obtain a polyamic acid aqueous solution;

[0065] (4) pouring the polyamic acid dispersion obtained in the above step 3 into a mold, placing the mold in a freezer, freezing at -70°C for 3 hours, and then placing the mold in a freeze dryer for freeze drying to obtain a polyamic acid aerogel;

[0066] (5) The polyamic acid aerogel obtained in the above step 4 is placed in a tubular furnace, and the polyamic acid is imidized by high temperature under an argon atmosphere. The high temperature treatment temperature program is 100° C. for 1 hour, 200° C. for 1 hour, and 300° C. for 1 hour, to finally obtain a polyimide aerogel.

[0067] The properties of the obtained polyimide / reduced graphene oxide composite aerogel were measured, and the results showed that the shape memory aerogel transition temperature was 280°C, the shrinkage rate was 24.6%, and the recovery rate of the first cycle was 48.7%.

[0068] Example 2

[0069] (1) Weigh 10 mmol ODA and 10.5 mmol BPDA. First, add 10 mmol ODA to 35 ml NMP in an ice bath and stir to dissolve. After dissolution, add 10.5 mmol BPDA in 5 equal portions and react for 3 hours. Then, add 3.1 ml triethylamine and continue to react for 9 hours to obtain a viscous polyimide precursor polyamic acid gel, which is placed in a refrigerator for aging for 24 hours before use.

[0070] (2) taking a large amount of ultrapure water and placing it in an ice bath, slowly pouring the polyamic acid gel obtained in the above step 1 into the ultrapure water and stirring it to obtain a filamentous gel, stirring it thoroughly, freezing the obtained filamentous gel at -20°C for 24 hours to obtain a frozen polyamic acid gel, placing it in a freeze dryer for freeze drying, and taking it out after 72 hours to obtain dry polyamic acid filaments;

[0071] (3) 0.455 g of the polyamic acid filaments obtained in step 2 above was dissolved in 20 ml of water, and 0.23 g of triethylamine was added to accelerate the dissolution to obtain a polyamic acid aqueous solution; 0.045 g of graphene oxide was added to the polyamic acid aqueous solution and stirred thoroughly to obtain a mixed dispersion of polyamic acid and graphene oxide;

[0072] (4) pouring the mixed dispersion of polyamic acid and graphene oxide obtained in the above step 3 into a mold, placing the mold in a freezer, freezing at -70°C for 3 hours, and then placing the mold in a freeze dryer for freeze drying to obtain a polyamic acid aerogel;

[0073] (5) The polyamic acid aerogel obtained in the above step 4 is placed in a tubular furnace, and the polyamic acid is imidized by high temperature under an argon atmosphere. The high temperature treatment temperature program is 100° C. for 1 hour, 200° C. for 1 hour, and 300° C. for 1 hour, to finally obtain a polyimide aerogel.

[0074] The properties of the obtained polyimide / reduced graphene oxide composite aerogel were measured, and the results showed that the shape memory aerogel transition temperature was 285°C, the shrinkage rate was 22.2%, and the recovery rate of the first cycle was 47.4%.

[0075] Example 3

[0076] (1) Weigh 10 mmol ODA and 10.5 mmol BPDA. First, add 10 mmol ODA to 35 ml NMP in an ice bath and stir to dissolve. After dissolution, add 10.5 mmol BPDA in 5 equal portions and react for 3 hours. Then, add 3.1 ml triethylamine and continue to react for 9 hours to obtain a viscous polyimide precursor polyamic acid gel, which is placed in a refrigerator for aging for 24 hours before use.

[0077] (2) taking a large amount of ultrapure water and placing it in an ice bath, slowly pouring the polyamic acid gel obtained in the above step 1 into the ultrapure water and stirring it to obtain a filamentous gel, stirring it thoroughly, freezing the obtained filamentous gel at -20°C for 24 hours to obtain a frozen polyamic acid gel, placing it in a freeze dryer for freeze drying, and taking it out after 72 hours to obtain dry polyamic acid filaments;

[0078] (3) 0.417 g of the polyamic acid filaments obtained in step 2 above was dissolved in 20 ml of water, and 0.21 g of triethylamine was added to accelerate the dissolution to obtain a polyamic acid aqueous solution, 0.083 g of graphene oxide was added to the polyamic acid aqueous solution, and the mixture was stirred thoroughly to obtain a mixed dispersion of polyamic acid and graphene oxide;

[0079] (4) pouring the mixed dispersion of polyamic acid and graphene oxide obtained in the above step 3 into a mold, placing the mold in a freezer, freezing at -70°C for 3 hours, and then placing the mold in a freeze dryer for freeze drying to obtain a polyamic acid and graphene oxide composite aerogel;

[0080] (5) The polyamic acid and graphene oxide composite aerogel obtained in the above step 4 is placed in a tubular furnace, and the polyamic acid is imidized and the graphene oxide is reduced by high temperature in an argon atmosphere. The high temperature treatment temperature program is 100° C. for 1 hour, 200° C. for 1 hour, and 300° C. for 1 hour, and finally a polyimide / reduced graphene oxide composite aerogel is obtained.

[0081] The properties of the obtained polyimide / reduced graphene oxide composite aerogel were measured. The results showed that the shape memory aerogel had a transition temperature of 301° C., a shrinkage rate of 19.33%, and a recovery rate of 50.2% in the first cycle. The overall performance was not as good as that of Example 1.

[0082] Example 4

[0083] (1) Weigh 10 mmol ODA and 10.5 mmol BPDA. First, add 10 mmol ODA to 35 ml NMP in an ice bath and stir to dissolve. After dissolution, add 10.5 mmol BPDA in 5 equal portions and react for 3 hours. Then, add 3.1 ml triethylamine and continue to react for 9 hours to obtain a viscous polyimide precursor polyamic acid gel, which is placed in a refrigerator for aging for 24 hours before use.

[0084] (2) taking a large amount of ultrapure water and placing it in an ice bath, slowly pouring the polyamic acid gel obtained in the above step 1 into the ultrapure water and stirring it to obtain a filamentous gel, stirring it thoroughly, freezing the obtained filamentous gel at -20°C for 24 hours to obtain a frozen polyamic acid gel, placing it in a freeze dryer for freeze drying, and taking it out after 72 hours to obtain dry polyamic acid filaments;

[0085] (3) 0.3 g of the polyamic acid filaments obtained in step 2 above was dissolved in 20 ml of water, and 0.15 g of triethylamine was added to accelerate the dissolution to obtain a polyamic acid aqueous solution, 0.2 g of graphene oxide was added to the polyamic acid aqueous solution, and the mixture was stirred thoroughly to obtain a mixed dispersion of polyamic acid and graphene oxide;

[0086] (4) pouring the mixed dispersion of polyamic acid and graphene oxide obtained in the above step 3 into a mold, placing the mold in a freezer, freezing at -70°C for 3 hours, and then placing the mold in a freeze dryer for freeze drying to obtain a polyamic acid and graphene oxide composite aerogel;

[0087] (5) The polyamic acid and graphene oxide composite aerogel obtained in the above step 4 is placed in a tubular furnace, and the polyamic acid is imidized and the graphene oxide is reduced by high temperature in an argon atmosphere. The high temperature treatment temperature program is 100° C. for 1 hour, 200° C. for 1 hour, and 300° C. for 1 hour, and finally a polyimide / reduced graphene oxide composite aerogel is obtained.

[0088] The properties of the obtained polyimide / reduced graphene oxide composite aerogel were measured. The results showed that the shape memory aerogel transition temperature was 296° C., the recovery rate of the first cycle was 16%, and the shape memory performance was not as good as that of Example 1.

Claims

1. A method for preparing a polyimide-based shape memory composite aerogel, characterized in that: The steps include: (1) a diamine monomer and a dianhydride monomer are subjected to a condensation polymerization reaction in N-methylpyrrolidone, and triethylamine is added after the reaction for 3 hours to obtain a polyimide precursor polyamic acid gel; (2) placing the obtained polyamic acid gel in water for solvent exchange, and then freeze-drying the gel to obtain polyamic acid filaments; (3) dispersing the obtained polyamic acid filaments, triethylamine and graphene oxide in water, and mixing them to obtain a mixed dispersion; the mass ratio of graphene oxide to polyamic acid filaments in the mixed dispersion is 1:4; (4) injecting the obtained mixed dispersion into a mold, placing the mold in a freezer for freeze molding, and freeze drying after molding to obtain a polyamic acid / graphene oxide composite aerogel; (5) The obtained polyamic acid / graphene oxide composite aerogel is subjected to high temperature treatment to obtain a polyimide / reduced graphene oxide composite aerogel, that is, a polyimide-based shape memory composite aerogel.

2. The method according to claim 1, characterized in that In step (1), the diamine monomer is 4,4'-diaminodiphenyl ether; and the dianhydride monomer is biphenyltetracarboxylic dianhydride.

3. The method according to claim 1, characterized in that In step (1), the molar ratio of the diamine monomer to the dianhydride monomer is 1:(0.8-1.5).

4. The method according to claim 1, characterized in that: In step (1), the molar ratio of triethylamine to diamine monomer is 1:(0.3-3.5).

5. The method according to claim 1, characterized in that In step (3), the mass fraction of graphene oxide in the mixed dispersion is 0.2%-1.0%.

6. The method according to claim 1, characterized in that In step (5), the temperature of high temperature treatment is 100-350° C. and the time is 1-3 hours.

7. The method according to claim 1, characterized in that In step (5), the high temperature treatment must be performed under an inert atmosphere.

8. A polyimide-based shape memory composite aerogel prepared by the method according to any one of claims 1 to 7.

9. Use of the polyimide-based shape memory composite aerogel according to claim 8 in the preparation of thermal insulation materials, sound insulation materials, flame retardant materials, flexible materials, shock absorbing materials and energy storage devices.

Citation Information

Patent Citations

  • Preparing method of polyimide aerogels and hybrid aerogels thereof

    CN106317407A